Anti-aging high-color-absorption hyperbranched nylon 6 resin and preparation method thereof

By using materials such as polybasic acid with eight-arm structure and 4-amino-2,2,6,6-tetramethylpiperidine, combined with ultraviolet absorbent and light shielding agent, aging-resistant hyperabsorbent hyperbranched nylon 6 resin was prepared by using materials such as polybasic acid with eight-arm structure and 4-amino-2,2,6,6-tetramethylpiperidine, combined with ultraviolet absorbent and light shielding agents, aging-resistant hyperabsorbent hyperbranched nylon 6 resin was prepared. , the problems of poor temperature resistance of branching agents and insufficient melt fluidity in the prior art have been solved, and high melt index and excellent processing performance have been achieved.

CN119285987AActive Publication Date: 2025-01-10JIANGSU HAIYANG CHEM FIBERS +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411817087.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-10
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing hyperbranched nylon 6 branching agent has poor temperature resistance, which leads to uncontrollable production process and low branching degree of polyether initiators, which limits the improvement of melt fluidity of branched nylon resin.

Method used

Caprolactam is used as polymer monomer, polybasic acid with an eight-arm structure is used as branching agent, 4-amino-2,2,6,6-tetramethylpiperidine is used as the capping agent, and high-temperature resistant ultraviolet absorber is added A light shielding agent is used to prepare aging-resistant hyperbranched nylon 6 resin by melt polycondensation.

Benefits of technology

It achieves high melt index, excellent melt flowability and processing performance, improves light stability and color absorption performance, extends the service life of the product, and significantly improves the aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285987A_ABST
    Figure CN119285987A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-aging hyper-branched nylon 6 resin with high color absorption and a preparation method of the anti-aging hyper-branched nylon 6 resin. The anti-aging high-color-absorption hyperbranched nylon 6 resin has the structural characteristics as shown in a formula I. The preparation method comprises the following steps: 1) selecting caprolactam as a polymeric monomer and polyacid with an eight-arm structure as a branching agent; 2) taking 4-amino-2, 2, 6, 6-tetramethylpiperidine as an end-capping reagent, and adding an ultraviolet absorbent and a light screening agent; and 3) carrying out melt polycondensation to obtain the anti-aging and high-color-absorption hyperbranched nylon 6 resin. The anti-aging and high-color-absorption hyperbranched nylon 6 resin provided by the invention has the characteristics of simple synthetic route, environment-friendly technical process, high melt flowability, excellent aging resistance, excellent physical and mechanical properties and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer and a preparation method thereof, and in particular to an aging-resistant, high-color-absorbing hyperbranched nylon 6 resin having simple synthesis route, environmentally friendly process, high melt fluidity, aging resistance, high color-absorbing performance and excellent physical and mechanical properties and a preparation method thereof. Background Art

[0002] Nylon is a general term for resins containing repeated amide groups -[NHCO]- on the molecular chain. It is the thermoplastic resin with the largest output, the most varieties, the widest application, and the best comprehensive performance among the five general engineering plastics. Common nylon resins (such as nylon 6, nylon 66, nylon 1010, etc.) are basically linear structures, while hyperbranched nylon is a new type of special nylon resin. Compared with linear nylons with the same molecular weight, its molecular surface has higher functionality, lower crystallinity, small fluid dynamics volume, low melt viscosity, and high melt fluidity. The most prominent feature is that the melt viscosity has nothing to do with the total molecular weight, but only depends on the molecular weight of each arm. The performance of hyperbranched nylon is different from that of linear nylon because it has a smaller atomic spatial arrangement size, a spherical symmetrical structure, smaller interactions between molecules, and no entanglement inside and outside the molecule. The solution and melt viscosity of hyperbranched nylon are much lower than those of linear nylon with the same molecular weight, and it has good wettability, making it particularly suitable for the preparation of highly filled composite materials. Its excellent fluidity expands the application areas of nylon materials, shortens processing cycles, and reduces system costs.

[0003] Chinese patent CN200710036035.0 discloses a method for synthesizing hyperbranched nylon 6, which uses dendritic macromolecule polyamide-amine (PAMAM) as a branching agent, and uses caprolactam and nylon 66 salt as polymerization monomers, and hydrolyzes and ring-opening polymerizes to obtain hyperbranched nylon 6, whose melt fluidity is 2 to 3 times that of ordinary nylon with similar mechanical properties, and has great improvements in the extrusion, spraying process and molding degree of the nylon device production process. However, the PAMAM branching agent selected in the patent has the defect of poor temperature resistance, and it has a multi-terminal amino structure, which may produce partial cross-linking with nylon 66 salt during the polymerization process, resulting in uncontrollable production process.

[0004] Chinese patent CN201110233490.6 discloses a method for preparing a branched nylon resin, comprising the following steps: mixing a lactam monomer, a catalyst and an initiator to obtain a first mixture, wherein the initiator is a polyether initiator and polyethyleneimine, and the polyether initiator is an amino-terminated polyether and a carboxyl-terminated polyether; heating the first mixture to 200-300°C, and the lactam monomer undergoes a ring-opening reaction to obtain a second mixture; and subjecting the second mixture to a condensation polymerization reaction to obtain a branched nylon resin. Compared with the prior art, the prepared branched nylon resin has a melt index of about 30g / 10min, and exhibits good toughness due to the presence of a polyether or polyethyleneimine structure with good flexibility and low glass transition temperature. However, due to the low degree of branching of the polyether initiator involved, the improvement of the melt fluidity of the branched nylon resin is relatively limited. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and develop an aging-resistant, highly color-absorbing hyperbranched nylon 6 resin with a simple synthesis route, an environmentally friendly process, high melt fluidity, aging resistance, easy color absorption performance and excellent physical and mechanical properties.

[0006] In order to achieve the purpose of the present invention, the overall inventive concept is: caprolactam is selected as a polymerization monomer, a polyacid with an eight-arm structure is used as a branching agent, 4-amino-2,2,6,6-tetramethylpiperidine is used as a capping agent, and an ultraviolet absorber and a light shielding agent are added, and an aging-resistant and highly color-absorbing hyperbranched nylon 6 resin can be obtained by melt polycondensation.

[0007] The present invention is achieved through the following technical solutions: A hyperbranched nylon 6 resin with high color absorption and anti-aging properties has the structural characteristics shown in formula I.

[0008]

[0009] Formula I A method for preparing an aging-resistant, highly color-absorbing hyperbranched nylon 6 resin comprises the following steps: 1) Caprolactam is selected as the polymerization monomer, a catalyst and an initiator are added, and a polyacid with an eight-arm structure is used as a branching agent; 2) Using 4-amino-2,2,6,6-tetramethylpiperidine as a capping agent, and adding a UV absorber and a light shielding agent; 3) Melt polycondensation can obtain aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0010] The catalyst is one of phosphoric acid, phosphorous acid and sodium hypophosphite, and the added amount is 0.1-0.5% of the mass of caprolactam.

[0011] The initiator mentioned above is water, and the added amount is 5-10% of the mass of caprolactam.

[0012] The structure of the polyacid having an eight-arm structure is one or two of those shown in Formula II, and the addition amount is 0.5-5.0% of the mass of caprolactam, preferably 1.0-3.0%.

[0013]

[0014] Formula II The added amount of the above-mentioned 4-amino-2,2,6,6-tetramethylpiperidine is 0.2-2.0% of the mass of caprolactam, preferably 0.5-1.5%.

[0015] The above-mentioned UV absorber is a high temperature resistant UV absorber, the temperature of 1% weight loss is ≥300℃, and is selected from DSunsorb TM UV-120, DSunsorb TM UV-360, DSunsorb TM UV-405, DSunsorb TM UV-1164, DSunsorb TM UV-1600, DSunsorb TM One or more of UV-3030, the addition amount is 0.5-1.0% of the mass of caprolactam.

[0016] The light shielding agent is one or more of nano carbon black, nano titanium dioxide, nano zinc oxide, and nano zinc barium, and the added amount is 1.0-2.0% of the mass of caprolactam.

[0017] The above-mentioned light shielding agent is surface-organically modified, and the surface organic modification is performed by one or more surfactants selected from DISPEBYK-180, DISPEBYK-190, and DISPEBYK-2012. The specific modification method is as follows: adding the light shielding agent, deionized water, and the surface modifier into a beaker in a mass ratio of 1:1-2:0.05-0.1, and dispersing them in a high-speed disperser at a speed of 800-1000r / min for 0.5-2 hours to obtain the light shielding agent after surface organic modification.

[0018] The specific process of the above-mentioned melt polycondensation is: after feeding, the air in the high-temperature and high-pressure reactor is replaced with high-purity nitrogen for 3 to 4 times, the temperature is raised to 205 to 220° C., the pressure in the reactor is maintained at 1.8 to 2.2 MPa, the pressure is maintained for 1.0 to 2.0 hours, the gas is slowly released, and the temperature is continued to be raised to 240 to 255° C., the pressure in the reactor is maintained at 2.2 to 2.5 MPa, the pressure is maintained for 1.0 to 2.0 hours, the gas is released to normal pressure, the water in the system is discharged, and then the system is gradually vacuumed to reduce the pressure to -0.05 to -0.09 MPa, and the material is discharged to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) A polyacid with an eight-arm structure was introduced as a branching agent, and a hyperbranched nylon 6 resin with a relative viscosity ≥ 2.0 and a melt index ≥ 40.0 g / 10 min was prepared by melt polycondensation. It exhibited excellent melt fluidity and processing properties and was particularly suitable for the production of highly filled modified engineering plastic products.

[0020] (2) Using 4-amino-2,2,6,6-tetramethylpiperidine as a capping agent and combining it with the high surface functionality of hyperbranched nylon 6 molecules, the photostability of hyperbranched nylon 6 resin can be improved at the molecular level, while the high content of terminal amino groups also improves the color absorption performance of the resin.

[0021] (3) By combining compounding technology with UV absorbers, light shielding agents and other functional additives, the aging resistance of hyperbranched nylon 6 resin can be further optimized, and there is almost no precipitation of functional additives, so the service life of the product is significantly extended. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the infrared curve of the aging-resistant, highly color-absorbing hyperbranched nylon 6 resin prepared in Example 1. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with specific embodiments.

[0024] Example 1: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.20 kg of polyacid with an eight-arm structure, 0.10 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TMUV-120, 0.20kg of surface organically modified nano titanium dioxide, were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210°C, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250°C, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa. The material was discharged to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin (its infrared curve is shown in FIG. Figure 1 as shown).

[0025] Example 2: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.30 kg of polyacid with an eight-arm structure, 0.10 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-120 and 0.20kg of surface organically modified nano titanium dioxide were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0026] Example 3: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.40 kg of polyacid with an eight-arm structure, 0.10 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-120 and 0.20kg of surface organically modified nano titanium dioxide were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0027] Example 4: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.50 kg of polyacid with an eight-arm structure, 0.10 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-120 and 0.20kg of surface organically modified nano titanium dioxide were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0028] Example 5: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.30 kg of polyacid with an eight-arm structure, 0.20 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-120 and 0.20kg of surface organically modified nano titanium dioxide were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0029] Example 6: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.30 kg of polyacid with an eight-arm structure, 0.20 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-405 and 0.20kg of surface organically modified nano titanium dioxide were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0030] Example 7: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.30 kg of polyacid with an eight-arm structure, 0.20 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-3030 and 0.20kg of surface organically modified nano titanium dioxide were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3 to 4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0031] Example 8: Weigh 20.00 kg of caprolactam, 0.03 kg of sodium hypophosphite, 1.200 kg of deionized water, 0.30 kg of polyacid with an eight-arm structure, 0.20 kg of end-capping agent 4-amino-2,2,6,6-tetramethylpiperidine, and 0.10 kg of high temperature resistant ultraviolet absorber DSunsorb in sequence. TM UV-3030 and 0.30kg of nano zinc barium with organic surface modification were put into a 50L high temperature and high pressure reactor, and the gas in the reactor was replaced with high purity nitrogen for 3-4 times. The temperature was raised to 210℃, the pressure in the reactor was maintained at 1.9MPa, the pressure was maintained for 1.5h, and the gas was slowly released. The temperature was further raised to 250℃, the pressure in the reactor was maintained at 2.2MPa, and the pressure was maintained for 1.0h, and the gas was released to normal pressure to discharge the water in the system, and then the system was gradually vacuumed to reduce the pressure to -0.07MPa, and the material was released to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

[0032] Among them, the polyacid with eight-arm structure used in Examples 1-4 is, The polyacid with an eight-arm structure used in Examples 5-8 is . In addition, the surface organically modified nano titanium dioxide used in Examples 1-7 and the surface organically modified nano zinc barium used in Example 8 are both modified with DISPEBYK-180. The specific modification method is: add the light shielding agent, deionized water and surface modifier into a beaker in a mass ratio of 1:2:0.05, and disperse them in a high-speed disperser at a speed of 800r / min for 1 hour to obtain the surface organically modified light shielding agent.

[0033] Comparative Example 1 Weigh 20.00kg of caprolactam, 0.03kg of sodium hypophosphite, and 1.200kg of deionized water in sequence, put them into a 50L high-temperature and high-pressure reactor, and use high-purity nitrogen to replace the gas in the reactor 3 to 4 times. Raise the temperature to 210℃, maintain the pressure in the reactor at 1.9MPa, maintain the pressure for 1.5h, slowly release the gas, and continue to raise the temperature to 250℃, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 1.0h, release the gas to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.07MPa, and discharge the material to obtain conventional nylon 6 resin.

[0034] Table 1 Performance data of the aging-resistant, highly color-absorbing hyperbranched nylon 6 resin prepared in each example and the comparative example Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Terminal amino content, mmol / kg 55 59 62 65 72 73 73 73 42 Melt index, g / 10min 42.5 54.8 63.8 69.2 70.4 70.5 70.3 70.7 17.8 Tensile strength, MPa 75.6 74.8 73.4 73.2 70.3 69.6 69.5 70.1 67.2 Elongation at break, % 19.2 18.8 18.7 18.5 17.3 17.5 17.1 17.6 16.4 Bending strength, MPa 96.2 95.8 95.1 94.2 92.0 91.8 91.6 91.2 89.4 Notched impact strength, MPa 8.2 8.0 7.9 7.6 6.9 6.7 6.8 6.4 6.1 Tensile strength after aging, MPa 70.2 69.6 68.8 68.1 68.8 68.2 67.8 68.4 47.1 Elongation at break after aging, % 18.1 17.9 17.5 17.2 16.8 16.9 16.7 17.0 10.2 Flexural strength after aging, MPa 90.0 89.2 89.0 88.5 87.9 87.5 87.1 87.0 68.5 Notched impact strength after aging, MPa 7.8 7.5 7.3 7.0 6.7 6.4 6.5 6.2 2.8 Color difference, nbs 4.3 4.4 4.5 4.7 3.4 3.6 3.3 3.1 12.5 Yellowness Index 5.1 5.2 5.4 5.6 4.3 4.7 4.4 4.9 15.8 Melt index test conditions: The pellets are placed in a constant temperature and humidity chamber for 24 hours and tested using a melt index meter. The test standard is GB / T 3682-2018.

[0035] Tensile strength and elongation at break test conditions: The tensile specimens were placed in a constant temperature and humidity chamber for 24 hours and tested using a testing machine. The test standard was GB / T 1040.2-2006.

[0036] Bending strength test conditions: The bending specimens were placed in a constant temperature and humidity chamber for 24 hours and tested using a testing machine. The test standard was GB / T 9341-2008.

[0037] Notched impact strength test conditions: The impact specimen is placed in a constant temperature and humidity chamber for 24 hours and tested using a testing machine. The test standard is GB / T 1043.1-2008.

[0038] Color difference test conditions: mainly use a colorimeter to measure the color changes of different samples before and after aging. What is measured is the straight-line distance between two different samples in the color space. The test standard is ASTM D2244.

[0039] Yellowness index test conditions: mainly use a colorimeter to measure the yellowing degree of different samples before and after aging, and the test standard is ASTM D6290.

[0040] This patent adopts ASTM G154 xenon arc lamp aging, the lamp tube is 340nm, simulates outdoor ultraviolet light, and performs aging treatment on nylon 6 and aging-resistant high color absorption hyperbranched nylon 6 resin.

[0041] It can be seen from the data in Table 1 that, compared with conventional nylon 6 resin, the physical and mechanical properties of the aging-resistant, highly color-absorbing hyperbranched nylon 6 resin involved in this patent before aging treatment are relatively close to those of conventional nylon 6 resin, but the melt index is increased by 2.4 to 4.0 times, showing excellent melt fluidity and processing performance, and is particularly suitable for the production of highly filled modified engineering plastic products; in addition, after aging treatment, the retention rate of the physical and mechanical properties of the aging-resistant, highly color-absorbing hyperbranched nylon 6 resin involved in this patent is basically around 90%, while the physical and mechanical properties of conventional nylon 6 resin decrease by more than 30%, and the color difference change and yellowness index of the aging-resistant, highly color-absorbing hyperbranched nylon 6 resin are significantly lower than those of conventional nylon 6 resin.

Claims

1. An aging-resistant, highly color-absorbing hyperbranched nylon 6 resin, characterized in that: The aging-resistant, highly color-absorbing hyperbranched nylon 6 resin has the structural characteristics shown in Formula I: Formula Ⅰ.

2. A method for preparing the aging-resistant, highly color-absorbing hyperbranched nylon 6 resin according to claim 1, characterized in that: The steps include: 1) Caprolactam is selected as the polymerization monomer, a catalyst and an initiator are added, and a polyacid with an eight-arm structure is used as a branching agent; 2) Using 4-amino-2,2,6,6-tetramethylpiperidine as a capping agent, and adding a UV absorber and a light shielding agent; 3) Melt polycondensation can obtain aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

3. The method according to claim 2, characterized in that The catalyst is one of phosphoric acid, phosphorous acid and sodium hypophosphite, and the added amount is 0.1-0.5% of the mass of caprolactam.

4. The method according to claim 2, characterized in that: The initiator is water, and the added amount is 5-10% of the mass of caprolactam.

5. The method according to claim 2, characterized in that: The structure of the polyacid having an eight-arm structure is one or a combination of two of the formulas shown in Formula II, and the added amount is 0.5-5.0% of the mass of caprolactam: Formula II.

6. The method according to claim 2, characterized in that The added amount of the 4-amino-2,2,6,6-tetramethylpiperidine is 0.2-2.0% of the mass of caprolactam.

7. The method according to claim 2, characterized in that: The ultraviolet absorber is a high temperature resistant ultraviolet absorber, the temperature of 1% weight loss is ≥300℃, and is selected from DSunsorb TM UV-120, DSunsorb TM UV-360, DSunsorb TM UV-405, DSunsorb TM UV-1164, DSunsorb TM UV-1600, DSunsorb TM One or more of UV-3030, the addition amount is 0.5-1.0% of the mass of caprolactam.

8. The method according to claim 2, characterized in that: The light shielding agent is one or more of nano carbon black, nano titanium dioxide, nano zinc oxide and nano zinc barium, and the added amount is 1.0-2.0% of the mass of caprolactam.

9. The method according to claim 2, characterized in that: The light shielding agent is surface-organically modified, and the surface organic modification is performed by one or more surfactants selected from DISPEBYK-180, DISPEBYK-190, and DISPEBYK-2012. The specific modification method is as follows: adding the light shielding agent, deionized water, and the surface modifier into a beaker in a mass ratio of 1:1-2:0.05-0.1, and dispersing them in a high-speed disperser at a speed of 800-1000 r / min for 0.5-2 hours to obtain the light shielding agent after surface organic modification.

10. The method according to claim 2, characterized in that The specific process of the melt polycondensation is: after feeding, the air in the high-temperature and high-pressure reactor is replaced with high-purity nitrogen for 3 to 4 times, the temperature is raised to 205 to 220° C., the pressure in the reactor is maintained at 1.8 to 2.2 MPa, the pressure is maintained for 1.0 to 2.0 hours, the gas is slowly released, and the temperature is continued to be raised to 240 to 255° C., the pressure in the reactor is maintained at 2.2 to 2.5 MPa, the pressure is maintained for 1.0 to 2.0 hours, the gas is released to normal pressure, the water in the system is discharged, and then vacuum is gradually drawn to reduce the pressure of the system to -0.05 to -0.09 MPa, and the material is discharged to obtain the aging-resistant and highly color-absorbing hyperbranched nylon 6 resin.

Citation Information

Patent Citations

  • Synthesis process for ultra-branching nylon 6

    CN101148507A

  • Preparation method of branched chain nylon resin

    CN102432869A

  • Nylon composition with long-term thermo-oxidative aging resistance

    CN115991934A

  • Transparent copolyamide resin and preparation method thereof

    CN116813903A

  • Flame-resistant polyamide as reaction product of a lactam, and method for the production and use thereof

    EP3328916A1